Notas botánicas sobre aislamiento y contacto. Plantas y vestigios hi-merimã (río Purús/ Amazonía brasileña) - Cangussu, Daniel (2021)
In order to recover, even partially, the memory of the intense relations that existed among the different Arawá people in the middle Purus region, this article explores, through the intertwining of human and plant life, the sociality that was broken, the stories that were once shared, but also the bonds that are still flourishing in the forests. The forester science, attentive to plants and anthropic vestiges present in the forests, shows unsuspected ways to analyze the complex relationships between the Hi-Merimã, who are now in isolation, and their neighbors, especially the Jamamadi. In this text, we propose an analysis of the narrative of an encounter through notes that demonstrate the centrality and fecundity of plants for the understanding of Hi-Merimã sociality and territorial dynamics. The notes are based on bibliographic data from anthropological, archeological and botanical studies, as well as information obtained from the indigenous peoples and river communities in the area.